DEPRESSION IN THE CONTINUOUS SPECTRUM OF SOLAR RADIATION IN THE REGION 6500 − 8200˚A - Stelmakh, O. M.; Tyshko, N. L. (Одеські астрономічні публікації, 2016)
Based on the authors’ computations of cross-sections of the basic processes which form continuous absorption in the photospheres of solar-type stars, the spectral dependence of the solar radiation intensity in the continuous spectrum in the visible and infrared regions has been investigated. It is shown that the depression observed in the continuous spectrum of solar radiation in the region (6500 − 8200) ˚A is caused by the processes of photoionization of neutral hydrogen atoms excited up to the energy levels with the principal quantum number n = 3. The results of computation are in good agreement with the data observed.